2022
DOI: 10.1097/mnm.0000000000001535
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry in Lu-177-PSMA-617 prostate-specific membrane antigen targeted radioligand therapy: a systematic review

Abstract: Background 177Lu-prostate-specific membrane antigen (PSMA) gained popularity as a choice of agent in the treatment of patients with advanced prostate cancer or metastatic castration-resistant stage of prostate carcinoma (mCRPC) diseases. However, this treatment may cause fatal effects, probably due to unintended irradiation of normal organs. We performed an extensive systematic review to assess the organs at risk and the absorbed dose received by tumor lesions in 177Lu-PSMA therapy. Design In this review, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
7
1
Order By: Relevance
“…Existing data on 177 Lu-PSMA-617 RLT dosimetry indicate that the radiation dose delivered to the target is key in ensuring response (21,22). However, in a recent systematic review, a relevant variability in tumor dose (range, 7.5-77.6 Gy) was highlighted across and within populations (23). Technical issues and differences in tracer uptake intensity could partly account for this variability.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data on 177 Lu-PSMA-617 RLT dosimetry indicate that the radiation dose delivered to the target is key in ensuring response (21,22). However, in a recent systematic review, a relevant variability in tumor dose (range, 7.5-77.6 Gy) was highlighted across and within populations (23). Technical issues and differences in tracer uptake intensity could partly account for this variability.…”
Section: Discussionmentioning
confidence: 99%
“…Similar absorbed doses to organs-at-risk have also been approximated when using [ 177 Lu]Lu-PSMA-I&T [ 75 , 81 , 98 , 123 126 ] (Annex Table- 5 ). The technical aspects of the respective studies have recently been summarized in a systematic review [ 127 ]. A comparative retrospective analysis, evaluating both radiopharmaceuticals with identical methods, confirmed the similarity of [ 177 Lu]Lu-PSMA-617 and [ 177 Lu]Lu-PSMA-I&T regarding organs at risk [ 2 ] but has the limitation of low patient numbers and retrospective matched-pair analysis.…”
Section: Dosimetrymentioning
confidence: 99%
“…Radiation safety precautions may be modeled after 177 Lu-DOTATATE therapy for neuroendocrine tumors given a shared radionuclide [ 26 , 34 ]. A recent meta-analysis of 177 Lu PSMA-617 dosimetry found that the lacrimal and salivary glands are the critical organs with the kidneys also receiving a significant radiation dose [ 35 ]. The calculated radiation absorbed doses to the lacrimal and salivary glands after 4 cycles of 177 Lu PSMA-617 is near the tolerated dose limit whereas the dose to the kidneys is far below the dose tolerance limits.…”
Section: Beta Emitting Psma Targeted Radiotherapeuticsmentioning
confidence: 99%